The effect of gestational age on mitochondrial properties of the mouse placenta. Issue 1 (17th February 2022) - Bartho, Lucy A; Fisher, Joshua J; Walton, Sarah L; Perkins, Anthony V; Cuffe, James S M
Abstract : Mitochondria are organelles within the cell that generate energy, which is essential to the developing placenta. As the placenta approaches term, organelles such as mitochondria and the endoplasmic reticulum adapt to cellular stressors (e.g. oxidative stress and fluctuations in oxygen concentration) which are likely to result in the progressive decline of tissue function, known as placental ageing. This ageing phenotype may induce cellular senescence, a process whereby the cell is no longer proliferating, yet remains metabolically active. Mitochondria, endoplasmic reticulum and senescent processes are still poorly understood in the developing placenta. Therefore, a rodent ontogeny model was used to measure genes and proteins involved in mitochondrial biogenesis, antioxidant function, electron transport chain, mitophagy, dynamics and unfolded protein response in the placenta. CD-1 mouse placental samples were collected at embryonic day (E)12.5, E14.5, E16.5 and E18.5 of pregnancy for gene and protein analysis via qPCR, protein assays and Western blotting. Mitochondrial content, SDHB (complex II) and MFN2 (mitochondrial fusion) proteins were all increased throughout pregnancy, while citrate synthase activity/mitochondrial content, Tfam, Sirt3, Mfn1, TOMM20 (mitochondrial biogenesis and dynamics); Tp53 (senescence) ; Eif2ak3, Eif4g1 (endoplasmic reticulum stress) ; NDUFB8, UQCRC2, ATP5A (electron transport chain sub-complexes) were decreased at E18.5, compared to E12.5. Overall, mitochondria undergo changes in response to gestational progression and pathways associated with cellular ageing to facilitate adaptions in a healthy pregnancy. This data holds great promise that mitochondrial markers across pregnancy may help to establish when a placenta is ageing inappropriately. Lay summary: Human pregnancy lasts approximately 266 days. If a baby is born early, organs may be poorly formed but if pregnancy continues past this time, stillbirth risk is increased. Gestational duration is regulated by the placenta. As the placenta approaches the end of pregnancy, it displays properties similar to tissues from aged individuals. However, it is unknown how this placental ageing contributes to pregnancy duration. This study characterised normal placental ageing by measuring properties of mitochondria in healthy placentas collected at four different gestational ages ranging from 7 days before birth to 1 day before birth of the 19-day mouse pregnancy. We found that mitochondrial number increased per cell but that a marker of mitochondrial function was reduced. Proteins that control mitochondrial number, morphology and function also changed over time. This work lays the platform to understand how placental ageing contributes to adverse pregnancy outcomes related to altered pregnancy duration.